Human capital investment with competitive labor search - Leo Kaas; Stefan Zink (Institute for the Study of Labor (IZA), 2008)
We study human capital accumulation in an environment of competitive search. Given that unemployed workers can default on their education loans, skilled individuals with a larger debt burden prefer riskier but better paid careers than is socially desirable. A higher level of employment risk in turn depresses the skill premium and the incentives to invest in education. The equilibrium allocation is characterized by too much unemployment, underinvestment by the poor, and too little investment in skill-intensive technologies. A public education system funded by graduate taxes can restore efficiency. More generally, differences in education funding can account for cross-country variations in wage inequality.
urn:nbn:de:101:1-20081014256
Keywords: I22; 330; Directed search; investment; education finance; Bildungsverhalten; Bildungsinvestition; Arbeitsuche; Wettbewerb; Bildungsfinanzierung; Allokationseffizienz; Öffentliche Bildungsausgaben; Theorie